Shifting The Existence Of Women In Bantengan Art In Batu City: A Study Of Gender Ethnography And Cultural Communication In Batu City - Siwandoyo, Eko Budi; Indah Lestari, Putri Ayu; Sukma, Ferry Indra (International Journal of Multidisciplinary Applied and Science Research, 2025)
This study examines the shifting role and visibility of women within the traditional performance art of Bantengan in Batu City, East Java. Historically dominated by male performers and imbued with spiritual-masculine symbolism, Bantengan has witnessed a notable increase in female participation in recent years. Employing a qualitative ethnographic approach, this research investigates how women’s involvement is perceived, negotiated, and integrated into this traditionally gendered cultural space. Data were collected through participant observation, in-depth interviews, and analysis of digital media content. The study is framed by Peter L. Berger’s theory of social construction to analyze the processes of externalization, objectivation, and internalization of women’s roles within the Bantengan community. Findings reveal that women’s participation not only challenges entrenched gender norms but also revitalizes the art form by attracting younger participants and fostering innovation. Social media platforms, particularly TikTok and Instagram, emerge as significant arenas for the normalization and legitimization of women’s presence in Bantengan, accelerating the community’s acceptance. This research contributes to the discourse on gender, cultural preservation, and digital mediation in traditional arts. It demonstrates that cultural sustainability in the contemporary era can be enhanced through inclusive practices and adaptive communication strategies, positioning women not merely as participants but as active agents in the ongoing transformation of intangible cultural heritage.